Characterization of canola growth and in-vivo element fate in Canadian prairie under the interferences of tillage and residue treatment. (20th October 2021) - Huang, Jing; Huang, Gordon; Xin, Xiaying; Halstead, David; Gaetz, Katelyn; Benmerrouche, Leila; Wu, Yuwei; Wang, Nan; Fu, Yupeng; Zhang, Jinbo
Abstract: Canola is one of the main crops produced in Canadian Prairie. It is important to provide an effective approach for improving the growth and yield of canola. The effects of tillage and residue management on the growth of canola have been analyzed in this study through evaluating physicochemical features of canola plants under the interferences of tillage and residue treatment. Synchrotron-based FTIR and X-ray Fluorescence Mapping technologies are used to examine the variation of different organisms and important metal elements in the canola plants at different stages. The effects of interactions among tillage and residue treatments on the growth state of canola plants at different growing stages are various. Content of lipid and protein in mature root are improved with the application of harrow treatment. The application of tillage management is beneficial for the content of some elements, while negatively influences the content of other metal elements. Graphical abstract: Image 1 Highlights: The interactive effects of tillage and residue treatment on canola growth was analyzed. Synchrotron-based FTIR were used to determine the variation of organic composite in canola. X-ray Fluorescence Mapping was used to reveal element changes in canola. The relationship between plant growth and element transport was discussed.